An Experimental Study on the Effect of Reflective Surface Variations on the Power Performance and Efficiency of Bifacial Solar Panel - Lastri Andini Gunawan; Jakariya; Ahmad Deni Mulyadi; Doane Puri Mustika; Dibyo Setiawan; Agus Subeno (Jurnal Konversi Energi dan Manufaktur, 2026)
The increasing demand for clean electrical energy in Indonesia highlights the need to optimize solar power generation technologies. Bifacial photovoltaic (PV) panels offer higher energy yield by utilizing solar radiation from both front and rear sides; however, their performance is strongly influenced by reflective properties of the surface beneath the panel. This study aims to analyze the effect of reflective surface variations with different albedo values on the power output and efficiency of bifacial solar panels under tropical rainy season conditions. An experimental method was employed using three identical bifacial PV modules (545 Wp) installed above asphalt, paving block, and white-painted surfaces. The modules were installed with a tilt angle of 8°, an azimuth angle of 0° (facing north), and a height of 60 cm above the surface. Measurements of solar irradiance, voltage, and current were conducted at irradiance levels ranging from 203 to 1001 W/m². Data were collected three days with same conditions and parameter in November 2024 during the period time from 09:00 to 15:00. The results show that to enhance rear-side irradiance, as indicated by the increase in output power observed in this study, leading to increased output power and efficiency. The white-painted surface produced the highest performance, achieving an average power increase of approximately 9.6% and a maximum efficiency of 16.3% compared to asphalt and paving block surfaces. These findings indicate that high-albedo surfaces are an effective solution for improving bifacial solar panel performance, particularly in wet tropical climates such as Bandung, Indonesia.